An Analysis of Illocutionary Act in “Frozen II” Movie - Wati, Refina; Siti Fitriani; Al Rosyidah, Afiifah (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
This study aims to analyze the types of illocutionary acts found in the main characters utterances in the